Health literacy: association with socioeconomic determinants and the use of health services in Spain - Tamayo-Fonseca, Nayara; Pereyra-Zamora, Pamela; Barona, Carmen; Mas, Rosa; Irles, Mª Ángeles; Nolasco, Andreu (Frontiers in Public Health, 2023)
Background Health literacy (HL) is the set of social and cognitive skills that determine person’s level of motivation and the ability to access, understand and use information to promote and maintain good health. The aim of this study is to assess the level of health literacy, and to analyze its relationship with sociodemographic variables, state of health, and use of health services in the population aged 15 and over in the Valencian Community (Spain). Methods Cross-sectional study based on a sample of 5,485 subjects participating in the Health Survey of the Valencia Community. The HLS-EU-Q16 was used. As outcome variables we considered HL categorized into 2 levels: Inadequate or Problematic HL and Sufficient HL and the standardized literacy index. Prevalence rates and HL means were estimated and OR were calculated to analyze the association between variables. Results A total of 12.8% of the subjects surveyed presented an inadequate or problematic degree of HL. This percentage was higher in people >85 years (63.1%), with a low level of education (46.5%), in retired people (27.4%) or in other work situations (25.0%), in foreigners (18.1%), in low-income people (16.2%), with a perception of poor health status (26.9%), chronic disease (18.5%) or with activity limitations (56.4% severe, 19.7% not severe). Significant differences were found. With the exception of chronic disease, all the variables analyzed were associated with HL. Low HL was associated with a lower consumption of medicines, a greater use of health services, general medical consultations, poorer knowledge of new health technologies and fewer preventive health visits. Conclusion The percentage of inadequate or problematic HL was globally not very high, but certain population subgroups notably presented a high degree of inadequate or problematic HL. Raising the HL level of such groups should be regarded as a priority. HL was shown to be associated with the service use and new health technology use. Enhancing the population’s HL should lead to the following: a greater probability of adopting preventive practices; improving the use of the health system; and boosting people’s abilities to manage and to improve their own health.